A directional control method for interface flow considering static voltage stability. (January 2015) - Mu, Yunfei; Jia, Hongjie; Zeng, Pingliang; Yu, Xiaodan; Xu, Tao
Highlights: A directional control method (DCM) for interface power flows is developed. A surface approximation approach is used to build the optimization model of DCM. The DCM is extended to dispatch generators considering static voltage stability. The DCM is used for online monitor and control of interface power flows. Abstract: A directional control method (DCM) for power flows on a set of interface lines between two regions of power system considering static voltage stability margin is developed in this paper. A surface approximation approach is firstly used to obtain the relationship between the interface flow solution and the generation direction of generator (the portion of generation variation in each participating generator to satisfy the desired power increase on the interface and the system loss). Then, an optimization model is built to determine the optimum dispatching scheme of generators. This method not only can control the total power on the interface to satisfy the power demand but also can realize the directional control of power on each interface line based on the needs of operation. The proposed DCM is further extended to determine the optimum dispatching scheme of generators for maximizing the interface flow margin (IFM), which is the active power margin of the key transmission lines between two regions of power system constrained by static voltage stability. A modified continuation power flow (MCPF) is used to show and evaluate the impacts of the DCM on the IFM. The New England 39-bus system and the IEEE 300-bus system have been employed to verify the effectiveness of the DCM.